1987
DOI: 10.1111/j.1600-9657.1987.tb00613.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary teeth traumatic injuries at a private pediatric dental center

Abstract: The purpose of this study was to analyze primary teeth traumatic injuries at a private pediatric dental center. A total of 114 children with 196 traumatized teeth participated in this study from 1980–1984. The most common injury was concussion. The 1–2 year olds presented the highest number of injuries (p<0.01). Falling against an object was the most common cause of injury in both sexes. Most of the injuries occurred inside the home. July and August were the months that showed the highest number of children wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
45
1
25

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 5 publications
18
45
1
25
Order By: Relevance
“…A few groups of authors 38,[40][41][42] have reported that the frequency of TDI increases in warm months in comparison with cold months. Our fi nding that traumas to deciduous teeth occurred in spring and summer months is in agreement with these reports.…”
Section: Discussionmentioning
confidence: 99%
“…A few groups of authors 38,[40][41][42] have reported that the frequency of TDI increases in warm months in comparison with cold months. Our fi nding that traumas to deciduous teeth occurred in spring and summer months is in agreement with these reports.…”
Section: Discussionmentioning
confidence: 99%
“…2 Intrusion injuries commonly occur in the primary dentition and account for 4% to 22% of damage to anterior primary teeth. [3][4][5][6][7][8][9][10][11][12] These injuries are more frequent in 1-3 year olds because of the high resilience and flexibility of the supporting structures around the primary teeth. 13 Intrusion is defined as luxation injury resulting from an axially directed impact which drives the tooth deeper into the alveolar socket and damages the periodontal ligament and neurovascular bundle fibres.…”
Section: Introductionmentioning
confidence: 99%
“…O tempo gasto entre o trauma e a procura por atendimento profissional foi um dado pesquisado em alguns estudos realizados em hospitais pediátricos, serviços públicos de atendimento odontológico e universidades e é relacionado ao nível de educação e à sensibilidade dos pais ou responsáveis pelos cuidados oral da criança (Garcia-Godoy; Garcia-Godoy, 1987). Uma pesquisa constatou que de 38,7% a 42% dos pacientes procuraram atendimento até 24 horas após o trauma (Garcia-Godoy; Garcia-Godoy, 1987;De Carvalho Rocha, 2002).…”
Section: Exodontia Devido Ao Traumatismo Dentalunclassified
“…Uma pesquisa constatou que de 38,7% a 42% dos pacientes procuraram atendimento até 24 horas após o trauma (Garcia-Godoy; Garcia-Godoy, 1987;De Carvalho Rocha, 2002). Estudos que avaliaram crianças 0 a 3 anos observaram que a maior procura acontece entre o 1º e 15º dia após o trauma (Cunha et al, 2001a;Avsar;Topaloglu, 2009 (Mactigue, 1999).…”
Section: Exodontia Devido Ao Traumatismo Dentalunclassified
See 1 more Smart Citation